Andean heritage, colonial heritage and miscegenation in Peru - Pereyra Plasencia, Hugo (Universidad del Pacífico, 1993)
The article discusses whether Peruvians have managed to forge a national identity similar to those found in Europe. The author maintains the Peruvian national identity does exist and comes across in a variety of forms. Nevertheless he also points out that this identity's distinctive trait is represented in the still delicate issue of racial mixing between Andean and pre-Hispanic cultures. For this reason it is not possible to talk about a national identity in the European sense.